Numerical simulation of laser cladding AlCrCuFeNi2 high-entropy alloy coatings. Issue 1 (1st June 2022) - Zhang, Zhiling; Yang, Honggang; Chen, Yunxia
Abstract: Laser cladding technology is an advanced material surface modification technology, which has the advantages of good combination of coating and substrate, and environmental protection process. In this paper, for the laser cladding of AlCrCuFeNi2 high-entropy alloy coatings, the effects of different laser powers and scanning speeds on the temperature and velocity fields were analyzed by numerical simulation. In the early stage of laser cladding process, heat transfer is dominated by heat conduction, and in the middle and later stages, convection dominates. Compared with the scanning speed, the laser power has a greater influence on the temperature peak inside the molten pool. The research results can provide a reference for the optimization of process parameters of laser cladding high-entropy alloy coatings.